Integrative analysis of metabolomics and transcriptomics reveals alterations in egg quality and hepatic lipid metabolism in hens supplemented with curcumin - Cunzhi Zou; Haiyu Jiang; Xuanfu Wu; Jiang Gao; Wenqiang Ma (Animal Nutrition, 2025)
Curcumin has been shown to affect lipid metabolism in various ways, but its molecular mechanisms in hens remain poorly understood. In this study, 378 Hy-Line Brown hens, aged 58 weeks, were randomly assigned into three groups, each consisting of 6 replicates with 21 hens per replicate. The control group was fed a basal diet, while the experimental groups received diets supplemented with either 50 or 100 mg/kg of curcumin for 42 days. The results indicated that 50 mg/kg curcumin supplementation significantly increased average egg weight (quadratically, P = 0.001) and decreased the feed conversion ratio (FCR) (quadratically, P = 0.018). Both 50 and 100 mg/kg curcumin supplementation increased the yolk weight (linearly, P = 0.010), yolk color score (linearly, P = 0.001), and thick albumin weight (quadratically, P = 0.003), thereby improving egg quality. Additionally, curcumin supplementation at both doses reduced hepatic triglyceride (TG) content (linearly, P = 0.007) and hepatic free cholesterol (FC) content (linearly, P = 0.003), while increasing serum catalase (CAT) activity (linearly, P = 0.008) and hepatic superoxide dismutase (SOD) activity (linearly, P = 0.013), alleviating hepatic steatosis and oxidative stress in laying hens. Transcriptomic analysis revealed that curcumin primarily upregulated key genes involved in hepatic cholesterol synthesis (Fdft1, Sqle, Cyp51A1, Msmo1, and Dhcr24) and downregulated key genes involved in hepatic TG synthesis (Acaca, Acacb, and Fasn). Metabolomic analysis identified upregulated serum lysoPS 18:1 as the most significant explanatory variable in curcumin-fed hens. Integrated metabolomics and transcriptomics further revealed that lysoPS 18:1 positively correlated with hepatic cholesterol synthesis genes (Fdft1, Sqle, Cyp51A1, and Msmo1) and negatively correlated with hepatic TG synthesis gene (Fasn), suggesting its role in reducing hepatic TG and FC metabolism. In conclusion, these findings indicate that curcumin enhances production performance and egg quality of laying hens, improves hepatic lipid metabolism, and that 50 mg/kg is the optimal supplementation dose.